Kisan credit card and smallholder farmers’ economic performance in eastern India: A panel data analysis - Sharma, Kriti; Kumar, Anjani; Agrawal, R.C. (International Food Policy Research Institute, 2025)
Farmers in India continue to be deprived of adequate and timely institutional credit. The Kisan Credit Card (KCC) scheme, introduced in 1998, sought to address this issue by providing credit support under a single window with simplified procedure. Using a panel data of 2,586 farming households from five states in Eastern India, namely, Bihar, Uttar Pradesh, Jharkhand, Odisha, and West Bengal in 2018 and 2023, we examine the determinants of access to KCC and its credit limit. We also analyze the impact of KCC on farmers’ input usage, dependence on moneylenders and farm income using propensity score weighted fixed effects model which controls for selection bias and unobservable time-invariant heterogeneities. We find that farmers’ participation in agricultural training, demonstrations and development programs encourage farmers to adopt KCC. Furthermore, KCC access increases farmers’ input usage and reduces their dependence on money lenders. This evidence comes from an economically challenged region whose economy significantly depends on agriculture. The findings of the study raise concerns over the limited penetration of the scheme among smaller-scale farmers and provide key insights into the underlying issues hindering the efficacious functioning of the scheme.